Digital Analysis of Closest Speaking Space in Dentates-Method Proposal and Preliminary Findings - Cristina Teodora Preoteasa; Karla Alexandra Duță; Bogdan Florin Tudose; Cătalina Murariu-Măgureanu; Elena Preoteasa (MDPI AG, 2024)
Aims: The aim of this study is to identify methods for the digital analysis of the closest speaking space in dentates and to assess certain particularities using digital analysis. Method: For the adult patients included in this study, traditional dental casts were fabricated, and interocclusal registrations of the maximal intercuspal position and of the closest speaking space were taken using polyvinyl siloxane. Dental casts in both positions were scanned using a dental laboratory scanner, and digital analysis was conducted using the 3Shape 3D Viewer. Results: The interocclusal distance corresponding to the closest speaking space can be easily and precisely measured digitally or assessed using occlusion maps, at the level of all teeth. The interocclusal distance was variable across the dental arch, central incisors, and second molars, registering the smallest values, and was asymmetrical, with mandibular lateral deviation being suggested. The assessment of the range of motion of the mandible during the speaking test, recorded based on tooth movement, was conducted using superimpositions. The movement of the tooth was the largest in central incisors and decreased progressively as the tooth was more distal, and, in all cases, mandibular deviation occurred, more frequently to the left. Conclusions: Digital methods for the analysis of the closest speaking space have the advantages of increased precision and a broader range of analysis and application, showing research and clinical value.